2003
DOI: 10.14209/jcis.2003.22
|View full text |Cite
|
Sign up to set email alerts
|

QoSOS: An Adaptable Architecture for QoS Provisioning in Network Operating Systems

Abstract: The increasing demand for distributed multimedia applications makes evident the need for end-to-end quality of service (QoS) provisioning. Pmticularly, operating systems, despite their location at end systems, switches or routers, must guarantee that resources under their control are adequately managed to fulfill the application requirements. This work proposes an architecture for adaptive QoS provisioning on network operating systems (QoSOS), focusing mainly on the packet queuing subsystem. The development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…When the RML isolate was inoculated into congenic and transgenic mice, increasing the number of copies of the a allele was found to be the major determinant in reducing the incubation time; however, increasing the number of copies of the b allele also reduced the incubation time, but not to the same extent as that seen with the a allele. From the foregoing investigations, we concluded that both Sinc and Prn-i are congruent with PrP (218), and recent gene targeting studies have confirmed this view (219).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…When the RML isolate was inoculated into congenic and transgenic mice, increasing the number of copies of the a allele was found to be the major determinant in reducing the incubation time; however, increasing the number of copies of the b allele also reduced the incubation time, but not to the same extent as that seen with the a allele. From the foregoing investigations, we concluded that both Sinc and Prn-i are congruent with PrP (218), and recent gene targeting studies have confirmed this view (219).…”
mentioning
confidence: 76%
“…The prototypic strains called Me7 and 22A gave incubation times of Ϸ150 and Ϸ400 days in C57BL mice, respectively (215, 268, 269). The PrP genes of C57BL and I͞Ln (and later VM) mice encode proteins differing at two residues and control scrapie incubation times (195,213,(217)(218)(219)270).…”
mentioning
confidence: 99%
“…Ablation of the Prnp gene renders mice unable to replicate murine-adapted scrapie strains (7), and increasing PrP overexpression levels in transgenic mice generally reduces the incubation time (8,9). Allelic forms of PrP have been linked to the disease susceptibility in several species including mice (10), sheep (11), and humans (12,13). The genetic linkage between familial TSEs and mutations in the human Prnp gene (14) also exemplifies the crucial role of PrP in TSEs.…”
mentioning
confidence: 99%
“…All cases of vCJD described to date have occurred in methionine homozygous individuals, a genotype shared by Ϸ40% of the British Caucasian population (10). In mice, two polymorphisms in the murine PrP gene (Prnp) have been described where Prnp a (Leu-108, Thr-189) and Prnp b (Phe-108, Val-189) are associated with short and long incubation times, respectively (6,(11)(12)(13).…”
mentioning
confidence: 99%